Hypoxia-Inducible Factor-1 as a Therapeutic Target in Endometrial Cancer Management - Laura M. S. Seeber; Ronald P. Zweemer; René H. M. Verheijen; Paul J. van Diest (Obstetrics and Gynecology International)
In the Western world, endometrial cancer (EC) is the most common malignant tumor of the female genital tract. Solid tumors like EC outgrow their vasculature resulting in hypoxia. Tumor hypoxia is important because it renders an aggressive phenotype and leads to radio- and chemo-therapy resistance. Hypoxia-inducible factor-1𝛼 (HIF-1𝛼) plays an essential role in the adaptive cellular response to hypoxia and is associated with poor clinical outcome in EC. Therefore, HIF-1 could be an attractive therapeutic target. Selective HIF-1 inhibitors have not been identified. A number of nonselective inhibitors which target signaling pathways upstream or downstream HIF-1 are known to decrease HIF-1𝛼 protein levels. In clinical trials for the treatment of advanced and/or recurrent EC are the topoisomerase I inhibitor Topotecan, mTOR-inhibitor Rapamycin, and angiogenesis inhibitor Bevacizumab. Preliminary data shows encouraging results for these agents. Further work is needed to identify selective HIF-1 inhibitors and to translate these into clinical trials.